Clinicopathological correlation between trophic-adipose levels and poor prognosis outcomes in Brazilian women diagnosed with breast cancer - Rech, Daniel; Tebaldi, Daniel G; Malanowski, Jessica; Scandolara, Thalita B; Jaques, Hellen dos Santos; Alves, Fernanda Mara; Teixeira, Gessica T; Silva, Janaína Carla da; Vasselai, Maria Eduarda; Moura, Juliana B; Damo, Rayana T; Panis, Carolina (Brazilian Journal of Oncology, 2021)
Objective: To describe the clinicopathological profile of breast cancer patients and association with excess body weight.Methods: This was a descriptive observational study of 126 women with breast cancer lesions treated between 2015 and 2017 at a cancer referral hospital for 27 municipalities in southwestern Paraná. Patients were categorized according to age at diagnosis, body mass index, menopausal status, molecular subtyping of tumors, histological characteristics, and risk stratification. Data were coded for analysis using the Statistical Package for Social Sciences (SPSS) 22.0.0 software.Results: There were 126 patients diagnosed with breast cancer and more than half of these had an excessive body weight (mean BMI 27.5kg/m2). There was a predominance of the triple negative molecular subtype in overweight women; they also had a higher frequency of tumors larger than 2cm and high histological grade tumors. There were significant associations in the overweight/ obese subgroup such as tumors in the intermediate grade luminal B subtype, presence of angiolymphatic emboli, and a high-risk of disease recurrence.Conclusion: The data indicate that being overweight is a determinant of worse prognosis in women with breast cancer in southwestern Paraná.
Keywords: Breast neoplasms; Obesity; Prognosis.